2016
DOI: 10.1016/s0959-8049(16)61352-7
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 dynamics influence mitotic slippage and death in mitosis

Abstract: Microtubule-binding drugs such as taxol are frontline treatments for a variety of cancers but exactly how they yield patient benefit is unclear. In cell culture, inhibiting microtubule dynamics prevents spindle assembly, leading to mitotic arrest followed by either apoptosis in mitosis or slippage, whereby a cell returns to interphase without dividing. Myeloid cell leukaemia-1 (Mcl-1), a pro-survival member of the Bcl-2 family central to the intrinsic apoptosis pathway, is degraded during a prolonged mitotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…15 MCL-1 is involved in regulation of both death in mitosis and death after mitotic slippage. [50][51][52] Mitotic degradation of MCL-1 can increase the probability of death in mitosis when MYC or NOXA is downregulated. 50,52 It can also hasten slippage during mitotic arrest caused by inhibitors of mitosis and increase the probability of apoptosis after slippage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 MCL-1 is involved in regulation of both death in mitosis and death after mitotic slippage. [50][51][52] Mitotic degradation of MCL-1 can increase the probability of death in mitosis when MYC or NOXA is downregulated. 50,52 It can also hasten slippage during mitotic arrest caused by inhibitors of mitosis and increase the probability of apoptosis after slippage.…”
Section: Discussionmentioning
confidence: 99%
“…50,52 It can also hasten slippage during mitotic arrest caused by inhibitors of mitosis and increase the probability of apoptosis after slippage. 51 While it is unclear if apoptosis induced by the belinostat-vincristine combination occurs during mitosis or after mitotic slippage, the concomitant downregulation of MCL-1 and upregulation of BIM could contribute to either.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 has a particularly short half-life, due to proteasomal degradation. This instability of Mcl-1, compared to other multi-domain Bcl-2 proteins, is exploited in mitotic cells to allow the loss of its anti-apoptotic activity over time (Harley et al, 2010;Wertz et al, 2011;Sloss et al, 2016). However, the mechanism controlling Mcl-1 degradation during mitosis is not as clear as that for cyclin B.…”
Section: Dynamic Regulation Of Priming During Mitosismentioning
confidence: 99%
“…The E3 ligase Mcl-1 ubiquitin ligase E3 (MULE) was shown to be important in Mcl-1 stability (Zhong et al, 2005), CDK1-mediated phosphorylation of Mcl-1 was shown to promote its degradation mediated by APC/C (Harley et al, 2010) and FBW-7/SCF, which targets Mcl-1 for ubiquitin-mediated degradation in interphase, was also shown to play a significant role in mitotic cells (Inuzuka et al, 2011;Wertz et al, 2011). However, a recent study has suggested that in colon carcinoma cell lines, none of these mechanisms has a dominant effect on promoting Mcl-1 loss during mitotic arrest (Sloss et al, 2016). Despite this lack of consensus as to the mechanism, it is clear that stabilisation of Mcl-1 in mitosis has a significant impact in delaying onset of DiM (Tunquist et al, 2010).…”
Section: Dynamic Regulation Of Priming During Mitosismentioning
confidence: 99%
See 1 more Smart Citation